Trends in behavioral and biological risk factors for non-communicable diseases among adults in Bhutan: results from cross-sectional surveys in 2007, 2014, and 2019 - Pengpid, Supa; Peltzer, Karl (Frontiers in Public Health, 2023)
Background The study aimed to evaluate trends in the prevalence and correlates of risk factors for non-communicable diseases (NCDs; low physical activity, insufficient fruit/vegetable intake, current tobacco use, problem alcohol use, diabetes, hypertension, increased total cholesterol, and obesity) in Bhutan. Methods Three repeat cross-sectional Bhutan STEPS surveys (N = 9,281) in 2007, 2014, and 2019 were analyzed. Results The proportion of people with 3–8 NCD risk factors significantly decreased from 62.8% in 2007 to 32.6% in 2019 (p < 0.001), and the mean number of NCD risk factors significantly decreased from 3.0 in 2007 to 2.1 in 2019 (p < 0.001). In linear regression analyses by study year, older age (p < 0.001) was positively associated with eight NCD risk factors across all study years. Furthermore, male subjects were negatively (p < 0.01) and positively (p < 0.001) associated with eight NCD risk factors, respectively. Higher education levels (p < 0.05) were positively associated with eight NCD risk factors in 2007 and negatively associated with eight NCD risk factors in 2019 (p < 0.05). Employment (p < 0.001) and urban residence (p < 0.001) were positively associated with eight risk factors for NCD in 2019, while urban residence (p < 0.001) was negatively associated with eight NCD risk factors in 2014. Conclusion The prevalence of eight NCD risk factors decreased in Bhutan over the past 13 years. Inadequate fruit and vegetable intake, problem alcohol use, and hypertension increased, current tobacco use, low physical activity, obesity, diabetes, and elevated total cholesterol decreased from 2007 to 2019. Several factors associated for eight and each individual NCD risk factor were identified, which can help guide interventions.